Effectiveness of the rifaximin for the treatment of irritable bowel syndrome - Rodríguez, Carlos (2019)
OBJECTIVE. To determine the efficacy and safety of rifamixin in a group of patients with diagnosis of irritable bowel syndrome. MATERIAL AND METHODS. It was carried out an observational, prospective, longitudinal, multicenter and descriptive study between March 2015 and January 2016. The study population were 18 yr-old or older attending to gastroenterologists‘ outpatient clinics. Patients met the inclusion criteria of Rome III as criterion diagnosis of IBS and subtypes. RESULTS. Two hundred twenty one patients were surveyed, of which 24 have not completed the follow-up visit and 14 sheets of data collection were not filled properly. Thus, the study contained 183 patients, of which 138 (75,4 %) were female. According to the Rome III criteria, 114 patients (62,3 %) had the diagnosis of IBS-D, 45 (24,59 %) IBS-C and 24 (13,1 %) SII-M. Remission of the bloating by each subtype at the end of the treatment occurred in 89,2 % (n = 91), 95,4 % (n =21) and 66,6 % (n = 30) for groups of IBS-D, IBS-IBS-M, respectively, and it was a trend that remained at the end of the track. Remission of the abdominal pain at the end of the treatment by each subtype occurred in: 84,0 % (n = 84), 95,2 % (n =20) and 91,1 % (n = 41) for groups of IBS-D, IBS-IBS-M, respectively, a trend that also remained at the end of the follow-up. Global remission of all symptoms at the end of the treatment and the follow-up was achieved in 94,5 % (n = 173) and 96,1 % (n = 176), respectively. Thirteen (7 %) of 183 patients reported adverse events, none of them was serious. CONCLUSIONS. Treatment with rifamixin turned out to be highly effective and safe in remission of abdominal pain and bloating in the three classical subtypes of IBS, as well as a global improvement all symptoms at the end of the treatment and after an average follow-up of two weeks.